2001
DOI: 10.1067/mtc.2001.112534
|View full text |Cite
|
Sign up to set email alerts
|

Proximal aortic dissection with coronary malperfusion: Presentation, management, and outcome

Abstract: As illustrated in this study, direct coronary repair is a safe alternative to bypass grafting. Aggressive myocardial resuscitation together with early operation is a key factor in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
3
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 10 publications
8
200
3
5
Order By: Relevance
“…36) Coronary obstruction is caused mostly by compression of ostium or proximal portion of coronary artery due to an expanded false lumen 36,37) or uncommonly by intimal flap 38) or disruption of the intima at the orifice. 36) Until recently, CAG has been the only measure for making the diagnosis of coronary artery involvement. Ramanath et al retrospectively analyzed 1343 AAAD cases and reported that preoperative CAG did not significantly increase in-hospital mortality (25.6% with CAG vs. 20.6% without CAG, P = 0.14).…”
Section: Coronary Arterymentioning
confidence: 99%
“…36) Coronary obstruction is caused mostly by compression of ostium or proximal portion of coronary artery due to an expanded false lumen 36,37) or uncommonly by intimal flap 38) or disruption of the intima at the orifice. 36) Until recently, CAG has been the only measure for making the diagnosis of coronary artery involvement. Ramanath et al retrospectively analyzed 1343 AAAD cases and reported that preoperative CAG did not significantly increase in-hospital mortality (25.6% with CAG vs. 20.6% without CAG, P = 0.14).…”
Section: Coronary Arterymentioning
confidence: 99%
“…Several case reports of a Stanford type A aortic dissection in combination with a myocardial infarction have been published. [1][2][3][4][5][6][7] In almost all cases the right coronary artery was involved. [1][2][3] We report a case of anterior myocardial infarction due to a Stanford type A aortic dissection involving the left main trunk of the coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mechanism, Neri et al 2) reported 3 types of coronary malperfusion. In the first case described above, the right coronary artery was classifi ed as type C malperfusion, namely, detachment of the coronary orifi ce, and the left main trunk was classifi ed as type B malperfusion, namely, dissection of the coronary artery.…”
Section: Case Reportmentioning
confidence: 99%
“…However, acute myocardial ischemia associated with aortic dissection is relatively rare and results in a critical condition of the patient [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%